2002
DOI: 10.1590/s1516-635x2002000100003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Temperature During the First Week of Brooding Period on Broiler Chick Body Weight, Viscera and Bone Development

Abstract: The objective of the present study was to assess the development of broiler chicks during the first week post-hatching when reared at three different environmental temperatures. A total of 480 day-old chicks were placed in three environmentally controlled rooms (20, 25 and 35°C) RESUMOO presente trabalho teve como objetivo estudar o efeito de diferentes temperaturas-ambiente durante a primeira semana de vida de pintos de corte sob parâmetros zootécnicos, desenvolvimento visceral e crescimento ósseo. Foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
9
0
3
Order By: Relevance
“…The fisher test showed a strong association between temperature and degree of swarm (Table 1) for experiment A (p < 0.001), in agreement with Vest (1997), Macari (1996), and Moraes et al (2002).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The fisher test showed a strong association between temperature and degree of swarm (Table 1) for experiment A (p < 0.001), in agreement with Vest (1997), Macari (1996), and Moraes et al (2002).…”
Section: Resultssupporting
confidence: 80%
“…Data on thermal comfort for young broilers are well documented in the literature and show that either the excess or the lack of heat during the first three weeks may lead to near 12% of body weight loss, affecting physiological variables such as heart beats and blood pressure (Vest, 1997;Hel et al, 1992;Macari et al, 1994;Dozier & Donald, 2001;Moraes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not determine the first 5 and 10 d feed intakes, lower body weights obtained on d 5 may indicate lower feed intake. Leksrisompong et al (2009) Moraes et al (2002) showed that relative yolk sac weight was not affected by brooding temperature. Similarly, our results showed that INC H chicks utilised yolk regardless of brooding temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores citam que o eixo longitudinal do galpão em climas quentes, deve seguir a orientação leste-oeste, visando uma menor entrada de radiação solar pelas laterais dos galpões e evitando a radiação direta sobre as aves, proporcionando melhor conforto térmico (Moraes, et al, 2002), conforme esquematizado na Figura 1:…”
Section: Influência Da Cobertura No Interior Das Instalaçõesunclassified